2011
DOI: 10.1016/j.farma.2010.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de la efectividad y la seguridad del natalizumab en el tratamiento de la esclerosis múltiple remitente recidivante

Abstract: The treatment's effectiveness and safety in our patient group suggest that natalizumab is a treatment for refractory patients or those with aggressive types of multiple sclerosis, although we do not yet know about its long-term effects and the evolution of the appearance of neutralising antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…Regarding disability, we observed that the decrease in EDSS score was greater than what was reported in Europe 21,26,30 , but lower than the results achieved in a study in Kuwait 34 . In addition, observational studies 7,26,27,28,29,30,31,32,33,34,35 have reported that between 9 and 57% of PwRMS experienced improvement of disability, while 4-17% had worsening of disability, which is consistent with our results. In this regard, a post hoc analysis within AFFIRM reported that PwRMS treated with natalizumab increased their cumulative likelihood of 12-week confirmed improvement of disability, compared with placebo at two years 36 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding disability, we observed that the decrease in EDSS score was greater than what was reported in Europe 21,26,30 , but lower than the results achieved in a study in Kuwait 34 . In addition, observational studies 7,26,27,28,29,30,31,32,33,34,35 have reported that between 9 and 57% of PwRMS experienced improvement of disability, while 4-17% had worsening of disability, which is consistent with our results. In this regard, a post hoc analysis within AFFIRM reported that PwRMS treated with natalizumab increased their cumulative likelihood of 12-week confirmed improvement of disability, compared with placebo at two years 36 .…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we observed that treatment with natalizumab significantly reduced the number of relapses at one and two years (93.9 and 92.9%, respectively). This was comparable with the 90.7% reduction in ARR achieved in TOP 32 and 83.2% in a recently published study in the US 6 , as well as in other observational studies 14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31 . In addition, the TOP study reported that PwRMS treated with natalizumab presented associations with reductions in relapse-related hospitalizations and steroid treatment, despite longer follow-up in the on-natalizumab period than in the pre-natalizumab period 33 .…”
Section: Discussionsupporting
confidence: 90%
“…Most published studies on this topic are descriptive [5,7,10-16]. Few research papers have attempted to correlate baseline data with outcome towards prediction of treatment response, and results are not always consistent between studies, possibly due to the methodological biases that might affect uncontrolled longitudinal studies.…”
Section: Discussionmentioning
confidence: 99%